Vaccine-Induced Immunological Memory in Invasive Fungal Infections – A Dream so Close yet so Far - Biswas, Partha S. (Frontiers in Immunology, 2021)
The invasive fungal infections (IFIs) are a major cause of mortality due to infectious disease worldwide. Majority of the IFIs are caused by opportunistic fungi including Candida, Aspergillus and Cryptococcus species. Lack of approved antifungal vaccines and the emergence of antifungal drug-resistant strains pose major constraints in controlling IFIs. A comprehensive understanding of the host immune response is required to develop novel fungal vaccines to prevent death from IFIs. In this review, we have discussed the challenges associated with the development of antifungal vaccines. We mentioned how host-pathogen interactions shape immunological memory and development of long-term protective immunity to IFIs. Furthermore, we underscored the contribution of long-lived innate and adaptive memory cells in protection against IFIs and summarized the current vaccine strategies.